Illuminating the need for a specific clinical care pathway for patients living with heart failure and identified as clinically frail. (2nd July 2022) - Lehane, M; Caples, N; Wassell, G
Abstract: Funding Acknowledgements: Type of funding sources: None. Background/Introduction: Against a background of increasing global population aging, frailty affects 8-10% of those over 65 years and 25-50% in those over 85 years. Frailty has a 4-6 times greater prevalence in heart failure patients and is increasingly recognised as a predictor of increasing hospitalisation and mortality in cardiovascular disease. The Rockwood Clinical Frailty Scale estimates an individual's degree of frailty on a scale of 1(very fit) to 9 (terminally ill) with a score of 5 or greater indicating frailty. Purpose: To estimate the 30-day prevalence of frailty in patients attending an ANP-led Heart Failure Clinic as a precursor to developing a clinical care pathway that systematically identifies frailty and triggers a comprehensive geriatric assessment. Methods: A multi-centre audit was conducted in three hospitals in Ireland. We retrospectively audited consecutive patients attending three ANP-led HF clinics in November 2021 to assess the prevalence of frailty. Demographic data, NYHA classification, number of hospital admissions in the previous year, clinical Frailty Score (CFS) and the number of patients under the care of a geriatrician was obtained from the medical notes of 170 heart failure patients consecutively reviewed. CFS was calculated in those patients over 65 years. Results: Of 376 HF reviews in November 2021, 170 individual patients were identified, 65% were male, 86% were aged 65ys or older of which 34% were over 80 years and a mean age of 73.4 years. 52% of the cohort were admitted at least once in the previous year of which 12% were admitted twice and 5% were admitted 3-4 times. 37% were classified as NYHA III and 0.6% were NYHA IV. The majority (68%) were newly diagnosed with HF within the previous year. 14% of patients were aged under 65yrs and did not have a CFS, 19% were deemed vulnerable (CFS 4), 41% were CFS 5 or greater and only 5% were under the care of a geriatrician. Conclusion(s): The prevalence of frailty (41%) was high in comparison with the national average of 24% and global average of 17%. Despite a strong association between age, frailty and heart failure, few patients were managed by a geriatrician. This audit emphasises the importance of developing a regional clinical care pathway that promptly recognises frailty in a high-risk population and triggers a comprehensive geriatric assessment. Furthermore, this audit highlights the limitations of the CFS in demonstrating cognitive and social vulnerability provoking further discourse in how patients are assessed and managed in the future.